Utilization of Ocean Current Energy in Awerange Bay as a Sustainable Alternative Energy Source (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
Indonesia has a sea area of ​​96,079 km2 and a coastline of 99,093 km, making Indonesia has the potential to utilize the sea as a new and renewable energy source. However, the use of new and renewable energy has only reached 6.2% in 2015. One of the marine energies that can be utilized is ocean currents. Awerange Bay, located in South Sulawesi, is a point that has a source of marine energy and can be used as an environmentally friendly, sustainable renewable energy. The current velocity in the Awerange Bay area in low tide can reach 0.25 - 0.36 m / s. So it can be possible to use tidal energy using turbines. The Kobold turbines take advantage of currents from seawater in Awerange Bay. By using a bi-directional (two-way) turbine that moves the turbine clockwise or vice versa. Turbines that are installed horizontally on the seabed can convert the kinetic energy of the turbines into electrical energy during tides, making the turbines suitable for use as marine tidal power generation. As a sample based on the Ministry of Energy and Mineral Resources, current energy can produce 1.2 MW / turbine. The big advantage of bi-directional turbines is that the propeller blades do not need to be reversed when the flow direction changes. This makes for a robust design, less expensive to build, maintain, and a lower risk of breakage. Also two-way turbines on average produce twice the electrical energy that uni-directional turbines, which only function during tides or floods.
Keywords: Renewable Energy, Tides, Kobold Turbines.